#TITLE_ALTERNATIVE# - RIDHO (12203024); Pembimbing: DR. Ir. Pudjo Sukarno dan DR. Ir. Asep KurniaPermadi, MUHAMMAD
An IPR curve (Inflow Performance Relationship) shows the behavior of well production. In this case, it shows the relationship between bottom hole pressures and fluid production rates. This paper presents one-phase dimensionless IPR curve (oil phase) for commingled systems without crossflow. A reservoir model was developed by CMG simulator in order to study the behavior of well performance. It was assumed that when the production testing was being run, all layers were tested at once, and then pressure gauge was positioned on the top of the upper layer. To develop this IPR, reservoir properties such as the number of layers, drainage radius, reservoir fluid/rock properties, and skin factor were varied. Because of one-phase IPR, the reservoir pressure must be higher than the bubble point pressure. This paper also presents the effect of unequal drainage radius and well position to estimate the contribution of each layer. Transmissivity ratio, i.e. the ratio between kh layer i with kh total, is used to estimate the contribution of each layer. In this specific case, this study considers only two-layered reservoirs as the model. In this study, a reservoir radial model was used employing synthetic data derived from many sources. The first goal of this paper is to give one-phase dimensionless IPR for commingled well that can be used to determine well performance when all layers are tested at once. Then, the second goal is to give an understanding that transmissivity ratio will give big deviation when it is applied to estimate the contribution of each layer which has unequal drainage radius.